2018
DOI: 10.1051/0004-6361/201732276
|View full text |Cite
|
Sign up to set email alerts
|

Determining the effects of clumping and porosity on the chemistry in a non-uniform AGB outflow

Abstract: Publisher rights © 2018 ESO. This work is made available online in accordance with the publisher's policies. Please refer to any applicable terms of use of the publisher. General rightsCopyright for the publications made accessible via the Queen's University Belfast Research Portal is retained by the author(s) and / or other copyright owners and it is a condition of accessing these publications that users recognise and abide by the legal requirements associated with these rights. ABSTRACTContext. In the inner… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 56 publications
(140 reference statements)
4
39
1
Order By: Relevance
“…We have presented the first model calculations that include the chemical effects of internal UV photons, here assumed to be blackbody radiation from cool AGB stars using the porosity formalism introduced by Van de Sande et al (2018b) and the CSE chemistry code from McElroy et al (2013). For the radiation fields used here, we find that internal photons are essentially unimportant at 10 −5 M ⊙ yr −1 due to the large value of dust extinction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have presented the first model calculations that include the chemical effects of internal UV photons, here assumed to be blackbody radiation from cool AGB stars using the porosity formalism introduced by Van de Sande et al (2018b) and the CSE chemistry code from McElroy et al (2013). For the radiation fields used here, we find that internal photons are essentially unimportant at 10 −5 M ⊙ yr −1 due to the large value of dust extinction.…”
Section: Discussionmentioning
confidence: 99%
“…At every radial distance r, we calculate the effective dust extinction in the porosity formalism, A eff V , in terms of the optical depth for a uniform outflow, A V . The equations for both a one-component model, where the inter-clump medium is void, and a two-component model, where mass is distributed in both a clump and inter-clump medium, are given in Appendix C of Van de Sande et al (2018b). The internal photon flux is diluted geometrically and extinguished by dust.…”
Section: Internal Uv and The Porosity Formalismmentioning
confidence: 99%
“…Some of the observed stars are likely to be characterised by a clumpy structure (Sloan et al 2016). Van de Sande et al (2018) showed that the optical depth is lower for clumpy mediums than in the homogeneous case for the same value of massloss rate. Thus, in case the medium is non-homogeneous, the DPR is probably underestimated under our assumptions.…”
Section: Iras Namementioning
confidence: 99%
“…It is also possible that a clumpy circumstellar medium accounts for some of the differences we see between the stars in our sample. For example, Van de Sande et al (2018b) show that clumpy outflows can produce a significant amount of CS. Various channel maps of other molecules towards R Dor show arc-like structures in the CSE rather than a smooth outflow, indicating a level of clumpiness in the outflow.…”
Section: Difference Between Lower and Higher Mass-loss Rate Starsmentioning
confidence: 99%